2014
DOI: 10.3201/eid2001.130858
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Barriers to Zoonotic Transmission of Prions

Abstract: Chronic wasting disease in elk might be a threat to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 39 publications
3
76
2
Order By: Relevance
“…This suggests that the known zoonotic potential of the BSE agent is recapitulated in this cell-free prion protein conversion assay irrespective of the host species (cow, sheep, or human). We have also shown that classical BSE cattle brain homogenates have a greater potential to convert human PrP C in PMCA than any other tested animal prion disease (39). Here we show that samples of experimental sheep BSE isolates of the VRQ/ VRQ, ARQ/ARQ, and ARR/ARR genotypes are all able to convert human PrP C during a single round of PMCA and that the preference is for the PRNP codon 129 M over the V allele (Table 1).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This suggests that the known zoonotic potential of the BSE agent is recapitulated in this cell-free prion protein conversion assay irrespective of the host species (cow, sheep, or human). We have also shown that classical BSE cattle brain homogenates have a greater potential to convert human PrP C in PMCA than any other tested animal prion disease (39). Here we show that samples of experimental sheep BSE isolates of the VRQ/ VRQ, ARQ/ARQ, and ARR/ARR genotypes are all able to convert human PrP C during a single round of PMCA and that the preference is for the PRNP codon 129 M over the V allele (Table 1).…”
Section: Discussionsupporting
confidence: 51%
“…The sCJD sample was from a patient with a diagnosis of sporadic CJD (VV2 subtype). The non-CJD human brain specimens used for PMCA substrate preparation were from frontal cortex from patients with Guillain-Barré syndrome (PRNP codon 129 MM) and dementia with Lewy bodies (PRNP codon 129 VV), and their use as PMCA substrates has been described previously (39).…”
Section: Methodsmentioning
confidence: 99%
“…Human prion proteinexpressing (PrP-expressing) transgenic mice resist CWD infection, suggesting a strong barrier for CWD transmission to humans (9)(10)(11)(12); however, certain non-human primates are CWD susceptible (13)(14)(15)(16). Similarly conflicting results from studies performed in vitro showed that CWD prions either efficiently or poorly convert human PrP to a pathogenic isoform (14,(17)(18)(19). Thus, no consensus has emerged on the susceptibility of humans to CWD prions, and the transmission of CWD to humans remains a major public health concern.…”
Section: Introductionmentioning
confidence: 75%
“…An alternative to modeling the species barrier is the cell-free conversion assay which points to CWD as the animal prion disease with the greatest zoonotic potential, after (and very much less than) BSE. 116 …”
Section: Emergence Of Novel Strainsmentioning
confidence: 99%